Selective Etching of N‐Doped Graphene Meshes as Metal‐Free Catalyst with Tunable Kinetics, High Activity and the Origin of New Catalytic Behaviors. (6th February 2018) - Dai, Yunqian; Zhou, Jie; Huang, Chengqian; Gu, Qing; Zeng, Yi; Xu, Wanlin; Meng, Xiangyu; Fu, Wanlin; Sun, Yueming
Abstract: New N‐doped reduced graphene oxide (N‐RGO) meshes are facile fabricated by selective etching of 3–5 nm nanopores, with controllable doping of N dopants at an ultrahigh N/C ratio up to 15.6 at%, from pristine graphene oxide sheets in one‐pot hydrothermal reaction. The N‐RGO meshes are illustrated to be an efficient metal‐free catalyst toward hydrogenation of 4‐nitrophenol, with new catalytic behaviors emerging in following three aspects: (i) tunable kinetics following pseudofirst order from commonly observed pseudozero order; (ii) strikingly improved activity with 26‐fold increased rate constant (1.0 s −1 g −1 L); (iii) no induction time required prior to reaction due to depressed back conversion, and dramatically decreased apparent activation energy ( E a ) (17 kJ mol −1 ). The origin of these new catalytic properties can be assigned to the synergetic effects between graphitic N doping and structural defects arising from nanopores. Deeper understanding unveils that the concentration of graphitic N is inverse proportion to E a, while the pyrrolic N has no impact on this reaction, and oxygenate groups hampers it. The porous nature allows the N‐RGO meshes to conduct catalyze reactions in continuous flow fashion. Abstract : New N‐doped reduced graphene oxide (N‐RGO )meshes are facile fabricated by selective etching of nanopores, with controllable doping of N dopants at an ultrahigh N/C ratio up to 15.6 at%. The N‐RGO meshes exhibit new catalytic behaviors, including tunable catalytic kinetics, strikingly improved activity, and unpredictable low apparent activation energy, due to the synergistic effect between defects and N‐dopants.